Evaluation of Acellular Bilayer Silk Fibroin Grafts for Onlay Tracheoplasty in a Rat Defect Model. (2nd October 2018) - Galvez Alegria, Cinthia; Gundogdu, Gokhan; Yang, Xuehui; Costa, Kyle; Mauney, Joshua R.
Abstract : Objective: To assess the efficacy of acellular bilayer silk fibroin (BLSF) grafts to repair full‐thickness tracheal defects and to compare the performance with conventional porcine small intestinal submucosa (SIS) implants. Study Design: A prospective controlled animal trial in a rat model of onlay tracheoplasty. Setting: Pediatric medical center. Subjects and Methods: Tracheal reconstruction of adult Sprague‐Dawley rats was performed with BLSF (n = 38) or SIS (n = 32) matrices for up to 3 months of implantation. Functional evaluations of repaired conduits as well as histologic, immunohistochemical, and histomorphometric analyses of neotissues were assessed. Results: Prior to scheduled euthanasia, survival rates of rats receiving BLSF or SIS grafts were ≥94%, with no clinical signs of airway obstruction observed over the course of the study. Micro–computed tomography analysis revealed that the mean percentage of stenosis was <20% in both implant groups. BLSF and SIS grafts supported formation of pseudostratified ciliated columnar epithelium by 1 week postoperatively; however, each matrix failed to promote de novo chondrogenesis by 3 months following repair. Conclusions: BLSF scaffolds can be used for reconstruction of rat tracheal patch defects with functional outcomes comparable to those of SIS matrices.